Proceedings of the 40th ACM Technical Symposium on Computer Science Education 2009
DOI: 10.1145/1508865.1508876
|View full text |Cite
|
Sign up to set email alerts
|

Successful and unsuccessful problem solving approaches of novice programmers

Abstract: Learning to program continues to be challenging for many students. This paper reports on problem-solving approaches undertaken by pair programming students. We examine reasons why some approaches lead to success while others lead to failure. We also identify some aspects of the Java language that appear to lead to student misconceptions. Finally, we provide suggestions for educators interested in helping students learn successful approaches and avoid unsuccessful ones.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 10 publications
(5 reference statements)
0
8
0
Order By: Relevance
“…Other scholars reached the same conclusion [31]. [3] noted that when programming students get stuck, they frequently search the textbook for solutions. [6] reported that their subjects read, looked information up on the Internet, and used tools.…”
Section: Literature Reviewmentioning
confidence: 63%
See 4 more Smart Citations
“…Other scholars reached the same conclusion [31]. [3] noted that when programming students get stuck, they frequently search the textbook for solutions. [6] reported that their subjects read, looked information up on the Internet, and used tools.…”
Section: Literature Reviewmentioning
confidence: 63%
“…Furthermore, instructors can ask capable students to help struggling students. This approach is referred to as pair programming and is encouraged by many educators as an effective learning tool [3,20]. Comments added to the complementary learning skills open-ended question emphasized the importance of learning the logic of programming.…”
Section: Results and Analysis Of Qualitative Datamentioning
confidence: 99%
See 3 more Smart Citations